Implementation of an In-depth Approach in Science Lessons for Fourth Grade Students of Nurul Yaqin Elementary School, Simpang Sungai Duren - Amirratul Soleha; Umil Muhsinin; Andi Nurhasanah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the implementation of a deep learning approach in improving the learning outcomes of IPAS among fourth-grade students at MIS Nurul Yaqin Simpang Sungai Duren. The research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected using essay tests and observation sheets. The results indicated a significant improvement in students’ learning outcomes, as reflected in the increase of the average score from 45 in the pre-cycle with 12% mastery, to 70 in Cycle I with 60% mastery, and further to 80 in Cycle II with 92% mastery. In addition, teacher activity improved from a score of 63 in the pre-cycle to 92 in Cycle II, while student activity increased from 69 in Cycle I to 82 in Cycle II. These findings demonstrate that the deep learning approach is effective in enhancing students’ learning outcomes, engagement, and conceptual understanding in IPAS learning.